2018
DOI: 10.1080/15389588.2017.1388915
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the protective capabilities of bicycle helmets in real-world and standard-specified impact scenarios

Abstract: The 10 bicycle helmets tested produced considerable differences in their protective capabilities under both real-world and standard-specified conditions on the CPSC rig. Risk of severe brain injury varied widely between helmets at the standard impact velocity, whereas the common, lower severity impacts produced PLAs associated with concussion. Helmets of a nonroad style generally performed worse across configuration. The temporal location produced higher risks for most helmets, although some helmets were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Several researchers have previously compared the performance of bicycle helmets in oblique impacts. 8,39,50,51 At present, the main resource to compare bicycle helmet performance in oblique impact testing is provided by the helmet laboratory at Virginia Tech University. They analyze linear acceleration and rotational velocity of the headform to derive a Summation of Tests for Analysis of Risk (STAR) score and a star rating, ranging from 0 to 5 stars.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have previously compared the performance of bicycle helmets in oblique impacts. 8,39,50,51 At present, the main resource to compare bicycle helmet performance in oblique impact testing is provided by the helmet laboratory at Virginia Tech University. They analyze linear acceleration and rotational velocity of the headform to derive a Summation of Tests for Analysis of Risk (STAR) score and a star rating, ranging from 0 to 5 stars.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work has shown that impacting this region at higher normal velocities (including those in standards) may cause some helmets to bottom out and produce extreme risk of injury. 3 The wide-ranging kinematics and concussion risks generated STAR values spanning from 10.9 to 25.3. A helmet's STAR value estimates the number of concussions that might occur out of all simulated impacts by combining the individual concussion risk from each impact with the relative real-world exposure of that impact.…”
Section: Discussionmentioning
confidence: 99%
“…The existing objective impact data comparing helmet models are either limited to standards testing or only evaluate a relatively small subset of helmets on the US market. 1,3,26,40 While most helmets are designed with similar materials, typically including a polycarbonate shell and expanded polystyrene (EPS) liner that permanently crushes to absorb energy upon impact, the many possible styles of bicycle helmets produce wide ranging design features, and previous research has demonstrated considerable differences in the ability of commercially-available helmets to reduce head injury risk. 1,3,26,40 To help reduce incidence of concussion in cycling and to stimulate improved helmet design for both mild and severe injury, consumers should have access to biomechanical data differentiating helmet performance that is informed by real-world cyclist impact conditions and injury mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Results are specific to impacts onto a 45°anvil covered with 80 grid sandpaper for consistency with precedence of prior studies. [5][6][7][8][9][10]17 A pilot study was conducted to explore the effect of sandpaper by impacting six additional Smith Maze helmets onto a 45°a nvil with a polished steel surface without sandpaper at 4.8 and 6.2 m/s at front, side and rear impact locations. Averaged across all impact scenarios, impacts without sandpaper yielded the same linear acceleration, a 9% lower rotational velocity, an 18% lower rotational acceleration, and a 16% lower probability of concussion than impacts with an 80 grid sandpaper.…”
Section: Biomedical Engineering Societymentioning
confidence: 99%
“…12 However, recent advances in helmet design suggest that the effectiveness of helmets may be further improved by targeted mitigation of rotational acceleration of the head. [8][9][10] Brain tissues are highly susceptible to rotational acceleration of the head, which subjects brain tissue to shear forces that can induce diffuse axonal injury. 16,18,22,29 Being incompressible, brain tissue has a high resistance to compressive forces associated with linear acceleration, but a very low resistance to shear forces associated with rotational acceleration.…”
Section: Introductionmentioning
confidence: 99%